Analyzing the Supply Potential and Demand for Wood Products in Ethiopia: A Review - Gemechu Kaba Sori; Azmera Belachew; Alemayehu Negassa; Omer Hinde; Eyuel Girmay (CV. Literasi Indonesia, 2023)
Ethiopia's growing population, urbanization, and booming construction industries are all factors in the country's rising demand for wood products. The country's current plantations are inadequate to meet the demand for wood products. The country only exports a small amount of wood, accounting for about 1.45% of all imports, while importing over 3 million m3 round wood equivalent (RWE), amounting to about USD 182.53 million. This showed that there is a large gap between import and export bills, which indicates a negative trade balance. The goal of this study is to examine supply patterns as well as existing and prospective demand for wood products, particularly industrial wood and wood fuel. First, a collection of all relevant documents indicating supply and demand was done. Then, two groups were created out of official records and study papers. Literature that is pertinent and related to the topic was chosen from among the groups. Different publications between 2010 and 2022 a total of 37 were utilized for this review. It was found that Ethiopia consumes more than 130 million m3/year of round wood equivalent, of which about 92.3% is used as wood fuel and the remaining is used to produce industrial goods with added value. Nowadays, imports provide a significant amount of Ethiopia's wood demand, and in 2015 alone, more than 30% of industrial needs were satisfied by imports. The review helps in determining the resource potential, supply-demand imbalance, and current level of demand for wood products.